A novel and fully scalable Agrobacterium spray‐based process for manufacturing cellulases and other cost‐sensitive proteins in plants. Issue 5 (2nd December 2014) - Hahn, Simone; Giritch, Anatoli; Bartels, Doreen; Bortesi, Luisa; Gleba, Yuri
Summary Transient transfection of plants by vacuum infiltration of Agrobacterium vectors represents the state of the art in plant‐based protein manufacturing; however, the complexity and cost of this approach restrict it to pharmaceutical proteins. We demonstrated that simple spraying of Nicotiana plants with Agrobacterium vectors in the presence of a surfactant can substitute for vacuum inoculation. When the T‐DNA of Agrobacterium encodes viral replicons capable of cell‐to‐cell movement, up to 90% of the leaf cells can be transfected and express a recombinant protein at levels up to 50% of total soluble protein. This simple, fast and indefinitely scalable process was successfully applied to produce cellulases, one of the most volume‐ and cost‐sensitive biotechnology products. We demonstrate here for the first time that representatives of all hydrolase classes necessary for cellulosic biomass decomposition can be expressed at high levels, stored as silage without significant loss of activity and then used directly as enzyme additives. This process enables production of cellulases, and other potential high‐volume products such as noncaloric sweetener thaumatin and antiviral protein griffithsin, at commodity agricultural prices and could find broad applicability in the large‐scale production of many other cost‐sensitive proteins.